Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/00918360903187853
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Family Environment on Future Mental Health Professionals' Attitudes Toward Lesbians and Gay Men

Abstract: This study explored the relationship between dimensions of functioning in the family of origin of graduate students in helping profession programs and their attitudes toward lesbians and gay men. One hundred forty-three participants completed the Family Environment Scale (FES-R: Moos & Moos, 1986), the Attitudes Toward Lesbians and Gay Men scale (ATLG: Herek, 1994), and demographic questions. Results suggest that three family dimensions (conflict, intellectual-cultural orientation, and moral-religious emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…Among graduate social work and counseling students assessed by the ATL and ATG, older students were more likely to hold negative attitudes toward gay men and lesbians (Kissinger et al, 2009). In another study of graduate students, though not exclusively in social work, 7% reported negative attitudes, which were significantly more likely among those who identified as conservative and religious, male, and, to a lesser extent, self-identified as African-Americans (Newman et al, 2002).…”
Section: Attitudes Among Graduate Students In Social Work and Other Fmentioning
confidence: 95%
See 4 more Smart Citations
“…Among graduate social work and counseling students assessed by the ATL and ATG, older students were more likely to hold negative attitudes toward gay men and lesbians (Kissinger et al, 2009). In another study of graduate students, though not exclusively in social work, 7% reported negative attitudes, which were significantly more likely among those who identified as conservative and religious, male, and, to a lesser extent, self-identified as African-Americans (Newman et al, 2002).…”
Section: Attitudes Among Graduate Students In Social Work and Other Fmentioning
confidence: 95%
“…Factor analyses have generated strong validity for the ATL and ATG (see Herek, 2004, for multiple citations;Cárdenas & Barrientos, 2008;Stoever & Morera, 2007) and convergent and discriminant validity has also been reported (Herek, 1984(Herek, , 1988(Herek, , 2006Kissinger et al, 2009). In addition, a test for socially desirable response bias demonstrated that this was not a factor in responses (Herek, 1998, as cited in Rosik, 2007.…”
Section: Attitudes Towards Lesbians and Gay Menmentioning
confidence: 99%
See 3 more Smart Citations